The Implementation of Early Childhood Prasiaga Paud in Developing Independence Attitudes of Early Childhood at RA Al Muhajirin Bekasi - Rustatik Rustatik; Rita Aryani (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
Scouting, introduced by the Dutch to Indonesia, serves as a foundational element for character and skill development. The scouting hierarchy includes Siaga for primary school and Prasiaga for Early Childhood Education (PAUD). This education approach aims to instill scouting values through play, fostering character, physical development, and the ability to do good deeds. In the context of early childhood, life skills play a crucial role in shaping their future. This research explores the implementation of Prasiaga scouting in developing life skills within the PAUD environment. Employing a qualitative approach with a case study focus, data collection methods include documentation and interviews with respondents. Thematic Data Analysis is applied to analyze the gathered data. The study is conducted at RA Al Muhajirin Bekasi Timur, with a sample population of approximately 50 respondents. The research findings indicate that Prasiaga activities effectively contribute to character and independence development among children at RA Al Muhajirin Bekasi Timur.